Turismo de sol e mar: empreendimentos turísticos imobiliários e o desenvolvimento urbano e socioeconomico no litoral do Ceará - o caso de Beberibe. - Novaes, Lucila Naiza Soares (2012)
This research aims to evaluate tourism as a vector for urban and socioeconomic development in the state of Ceará, with focus on the recently implemented touristic real estate projects and public investments in infrastructure on the coastal zone between the years 1995 and 2010, which correspond to the beginning of the operation of such structures. At first, theoretical and conceptual issues related to tourism and urban and socioeconomic development of touristic places are addressed, in order to enhance the understanding of the process of growth of such activity and, as a consequence to that fact, the implementation process of touristic projects in the areas of greater touristic attractiveness, the coastal zone of Ceará. Public policy and legislation aimed at the promotion of tourism in a local and national level are evaluated, taking into consideration the incentives directed towards it and how that practice has become a vector for the development of the state of Ceará. The study has chosen the municipality of Beberibe as a case study because of the concentration of touristic projects on its sea coast. These projects are geographically indicated, and their characteristics and relations with the municipality are addressed, relating the evolution of Beberibe and the current infrastructure to the urban, social and economic indicators. The study has identified the natural potential of the municipality of Beberibe for tourism of “sun and sea” and the growth of the flow of tourists to it, which, together, fostered the development of touristic activities, the implementation of touristic infrastructure and ultimately better quality of life to its inhabitants. That effort was made possible through comparison of Beberibe’s main indicators to the indicators of other municipalities of the state of Ceará, including the quality of urban infrastructure regarding road access, the growth of GDP per capita and local tax revenue, among others. The reason for better indicators was, for the most part, due to the contribution of tourism, which confirmed the stated hypothesis, since there was no other significant fact that could explain the push in Beberibe’s economy, besides the activities and services of the touristic production chain.